An experimental investigation into the anisotropic behaviour of bovine femoral cortical bone - Roginsky, Andrew (Blast Impact and Survivability Research Unit, 2017)
To increase our level of knowledge of the human body for various applications, the behaviour of cortical bone needs to be understood. To understand and model the behaviour of cortical bone, knowledge of the strain rate dependent behaviour is required. Many authors have investigated these properties, however, the literature appears to be ambiguous and incomplete, with little focus being placed upon the intermediate strain rate regime (1s⁻¹ to 100s⁻¹). The ambiguity arises as each author presents an averaged data set which does not describe the level of scatter or precise testing methods, nor does it correspond with other authors work [33, 56, 27, 2, 62]. Furthermore, bone should display distinct anisotropic properties due to the microstructural layout. However, no author has published or recorded a complete data set detailing the anisotropy of bone across any species. The intermediate strain rate regime is of particular interest due to Paul [50], capturing a distinct transitional behaviour of cortical bone between low and high strain rates. The apparent lack in intermediate regime research is due to the difficulty in attaining constant strain rate testing conditions within this region using conventional methods. Consequently, due to the absence of data, no accurate model has been developed to simulate the behaviour observed. The focus of this dissertation will therefore be to redesign and fabricate the previously used intermediate strain rate testing device, provide an accurate data set across both quasi-static and dynamic regimes, and a phenomenological model which is able to capture this strain rate dependent behaviour. In order to develop an understanding of the scatter presented in each orientation, light microscopy, inverse light microscopy, and SEM of the specimens is performed. What is observed is that each orientation displays a distinct microstructural layout with fractures propagating in a distinctly different manner based on the strain rate regime. Furthermore, counter to previous findings, the strength of bone across a variety of samples does not appear consistent, however, the longitudinal and radial orientations still display strain rate sensitivity (per sample) which was captured using the improved phenomenological viscoelastic model.